Design and pilot test of an implicit bias mitigation curriculum for clinicians - Svetkey, Laura P.; Bennett, Gary G.; Reese, Benjamin; Corsino, Leonor; Pinheiro, Sandro O.; Fischer, Jonathan E.; Seidenstein, Judy; Olsen, Maren K.; Brown, Tyson; Ezem, Natalie; Liu, Evan; Majors, Alesha; et al. (Frontiers in Medicine, 2024)
Introduction: Clinician implicit racial bias (IB) may lead to lower quality care and adverse health outcomes for Black patients. Educational efforts to train clinicians to mitigate IB vary widely and have insufficient evidence of impact. We developed and pilot-tested an evidencebased clinician IB curriculum, "REACHing Equity".To assess acceptability and feasibility, we conducted an uncontrolled one-arm pilot trial with post-intervention assessments. REACHing Equity is designed for clinicians to: 1) acquire knowledge about IB and its impact on healthcare, 2) increase awareness of one's own capacity for IB, and 3) develop skills to mitigate IB in the clinical encounter. We delivered REACHing Equity virtually in three facilitated, interactive sessions over 7-9 weeks. Participants were health care providers who completed baseline and end-of-study evaluation surveys.